Progestin and Nuclear Progestin Receptor Are Essential for Upregulation of Metalloproteinase in Zebrafish Preovulatory Follicles - Liu, Dong Teng; Carter, Nichole J.; Wu, Xin Jun; Hong, Wan Shu; Chen, Shi Xi; Zhu, Yong (Frontiers in Endocrinology, 2018)
Ovulation requires proteinases to promote the rupture of ovarian follicles. However, the identity of these proteinases remains unclear. In our previous studies using RNA-seq analysis of differential expressed genes, we found significant down-regulation of five metalloproteinases: adam8b (a disintegrin and metalloproteinase domain 8b), adamts8a (a disintegrin and metalloproteinase with thrombospondin motif 8a), adamts9, mmp2 (matrix metalloproteinase 2), and mmp9 in the nuclear progestin receptor knockout (pgr−/−) zebrafish that have failed to ovulate. We hypothesize that these metalloproteinases are responsible for ovulation and are regulated by progestin and Pgr. In this study, we first determined the expression of these five metalloproteinases and adamts1 in preovulatory follicles at different times within the spawning cycle in pgr−/− and wildtype (wt) zebrafish and under varying hormonal treatments. We found that transcripts of adam8b, adamts1, adamts9, and mmp9 increased drastically in the preovulatory follicular cells of wt female zebrafish, while changes of adamts8a and mmp2 were not significant. This increase of adam8b, adamts9, and mmp9 was significantly reduced in pgr−/−, whereas expression of adamts1 was not affected in pgr−/− zebrafish. Among upregulated metalloproteinases, adamts9 mRNA was found to be expressed specifically in follicular cells. Strong immunostaining of Adamts9 protein was observed in the follicular cells of wt fish, and this expression was reduced drastically in pgr−/−. Interestingly, about an hour prior to the increase of metalloproteinases in wt fish, both Pgr transcript and protein increased transiently in preovulatory follicular cells. The results from in vitro experiments showed that adamts9 expression markedly increased in a dose, time and Pgr-dependent manner when preovulatory follicles were exposed to a progestin, 17α,20β-dihydroxy-4-pregnen-3-one (DHP). Taken together, our results provide the first evidence that upregulation of adamts9 occurs specifically in preovulatory follicular cells of zebrafish prior to ovulation. Progestin and its receptor (Pgr) are essential for the upregulation of metalloproteinases.